Trend in Traditional Medicine Research as an Alternative Treatment for Lung Cancer: Bibliometric Analysis 2015-2024 - Farid, Muhammad; Hasan, Mailia Zulfa; Solikhah, Solikhah; Irham, Lalu Muhammad (Scripta Medica, 2025)
Lung cancer, a leading cause of death, is influenced by smoking. Treatment includes conventional and alternative therapies, with traditional medicine showing potential in overcoming resistance and improving patient prognosis. This study explored the trends and developments in research related to traditional medicine as an alternative therapy for lung cancer through bibliometric analysis during the period 2015–2024. Data were obtained from the Scopus database, resulting in 349 relevant documents. Analysis using VOSviewer and R Studio software showed a significant increase in the number of publications, with a peak in 2024. This article identified contributions from 1,839 authors and 177 sources, with the Journal of Ethnopharmacology as the main contributor. Keywords such as "lung cancer," "apoptosis" and "anticancer" were frequently used, reflecting the research focus on the molecular mechanisms and potential of traditional medicine. China and India dominated the global contributions, followed by the United States. International collaboration also played an important role in the development of research. The results showed that traditional medicine, including traditional Chinese medicine (TCM) and active compounds from spices such as curcumin, have the potential to inhibit cancer cell proliferation, enhance apoptosis and overcome drug resistance. This study underscores the importance of a multidisciplinary approach to exploring traditional medicine in lung cancer therapy.
Keywords: Medicine, traditional; Lung neoplasms; Bibliometrics